Tinjauan Bagi Hasil (Nisbah) Akad Mudharabah dalam Fatwa Ulama Dan Praktik Perbankan Syariah - Astuti, Afni Wiji; Irkhami, Nafis (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
The development of sharia economics in Indonesia is currently increasingly widespread and known by the public. Sharia Economics is one of the choices of people who want muamalah free from elements prohibited by religion. One of the choices of muamalah with the aim of Profit and Loss Sharing (PLS) is to use the Mudharabah Contract. This journal tries to examine how the division of the mudharabah contract ratio according to the views of Ulama with studies in Islamic banking. The research method used is a library research method using qualitative data. The results of the analysis show that the division of the ratio in the mudharabah contract, both according to the views of Ulama and Islamic banking, is based on the agreement of both parties making the contract, with the percentage or amount agreed upon at the time of the contract as in several examples of transactions.